Achievement of Control of Severe Bronchial Asthma When Using Dupilumab - O. V. Kazmerchuk; E. A. Sobko; I. V. Demko (Архивъ внутренней медицины)
The aim of the study was to evaluate the possibility of achieving control of severe bronchial asthma (BA) using genetically engineered biological therapy with Dupilumab.   Materials and methods. The study included 32 patients with severe bronchial asthma (8 (25 %) men, mean age 58 [28; 65]) years, 24 (75 %) women, mean age 50 [26; 62] years) who received additional therapy with Dupilumab for 12 months. The endpoint of the study was 12 months of therapy with Dupilumab. The allergic phenotype of the disease was recorded in 19 (60 %) patients, a quarter of patients had non-allergic phenotype, and 5 (15 %) patients had mixed BA.   Results. Before the introduction of genetically engineered biological therapy, patients had an extremely high daily need for emergency medications — about 9 times a day, 4 or more exacerbations were recorded during the previous 12 months before inclusion in the study. After 12 months of additional therapy with Dupilumab, a significant reduction in symptoms was noted — 22 (70 %) patients did not have asthma attacks at all. In 6 patients (19 %), 1 exacerbation of bronchial asthma developed during the next 12 months, which the patients coped with independently using nebulizer therapy at home. Before the start of genetically engineered biological therapy, 10 people (31 %) received systemic glucocorticosteroids (OCS) at a dose of 10 to 5 mg of prednisolone. After 4 months, 22 (70 %) patients receiving hormonal drugs managed to stop them. After 12 months, no patients took OCS.   Conclusion. During 12 months of additional therapy with Dupilumab, patients managed to completely stop taking OCS. Exacerbations requiring hospitalization were absent in all patients included in the study. Complete control was achieved by 22 (69 %) subjects, partial control was achieved by 10 (31 %). There was no need for short-acting beta-agonists (SABA) in 27 (85 %) subjects.